(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
A movie or a play is said to be great if it can imprint an image in our mind forever. To accomplish this, even the unnatural looking characters should look real. This case report describes a temporary prosthesis which alters the look of a theatre artist suited as a Dracula. Mock wax-up was done on the stone cast and an index of same was made using putty material. After dewaxingof the cast, tooth colored self-cure acrylic resin was mixed and poured into the index and stone cast with separating medium applied over it was pressed into the index. Prosthesis was retrieved, trimmed, polished and then delivered to patient.